A study of overcrowding factors in public low-cost housing in Malaysia - Nur Farhana Azmi,; Siti Najeeah Ruslee,; Yong Adilah Shamsul Harumain,; Syahrul Nizam Kamaruzzaman,; Chua, Shirley Jin Lin; Cheong, Au-Yong Peng (Penerbit Universiti Kebangsaan Malaysia, 2019)
The provision of affordable and quality housing has been a major focus of the Malaysian government in ensuring the overall well-being of households, especially for the B40 groups. Despite efforts by the government many of these buildings are overcrowded, and thus are inimical to people’s health and wellbeing. Therefore, this study attempts to identify the contributing factors that cause overcrowding problems which affect the occupants’ quality of life. A survey questionnaire has been conducted based on122 households from two different public low-cost housing in the Federal Territory of Kuala Lumpur, Malaysia, examining the causes that lead to cramped living conditions. Using the quantitative Statistical Package for the Social Sciences (SPSS) software, the study demonstrates that proximity to workplace and expensive rental housing as the main factors that contribute to overcrowding problems. The result also shows that a majority of the residents disagree with the current standard of measuring overcrowding. This implies loophole in the existing mechanism of controlling overcrowding. This paper concludes with the recommendation that the approach to overcome overcrowding problems should seek not only the perceptions of the decision making groups but also from the public at large.